PENGEMBANGAN LKS IPA TERPADU KONTEKSTUAL BERMUATAN LITERASI TEMA PEMANFAATAN TEKANAN DALAM KEHIDUPAN UNTUK PEMBELAJARAN SISWA SMP KELAS VIII - Putri Dwi Sari; Asrizal Asrizal; Letmi Dwiridal (PILLAR OF PHYSICS EDUCATION, 2017)
Science learning in 2013 curriculum is conducted in integrated form. On the other hand literacy skill is important for students in their learning and life. But the reality shows that science learning and student literacy aren’t implemented well yet. As solution of this problem is to develop contextual integrated science student worksheet by integrating literacy. The purpose of the research is to determine the validity, practicality and effectiveness of the integrated science student worksheet in scientific approach. The type of research is Research and Development (R & D).  Research design in preliminary testing was before and after treatment. Instruments to collect data were expert validity sheet,  practicality of test sheet, effectiveness of test sheet, attitude observastion sheet, and skill assessment sheet. Data analysis techniques which were used in this research were descriptive statistic analysis, graph method, and compare mean test. Based on data analysis, there were two of research results. First, contextual integrated science student worksheet by integrating literacy was very valid with average value is 92,0. Second, implemention of contextual integrated science student worksheet by integrating literacy was very practice acording teacher and students with average value of practicality respectly 87,0 and 84,6. Implementation of contextual integrated science student worksheet by integrating literacy was effective in science approach to improve student literacy